저 준위 액체섬광계수기를 이용한 섬광체 종류에 따른 222 Rn 농도 변화 연구 - 전재완; Jaewan Jeon; 이득희; Deuk-hee Lee; 김진섭; Jin-seop Kim (한국방사선학회 논문지, 2019)
오늘날 경제의 발전과 함께 여러 가지 환경 문제가 발생했다. 자연스레 사람들은 환경에 대한 관심이 높아졌으며 특히 식수에 대한 안전성과 오염도 조사에 대한 중요성이 부각되고 있다. 우리나라 국민들이 식수로 이용하는 지하수에서 우라늄 및 222 Rn 이 다수 지역에서 검출되고 있다. 따라서 이 연구는 지하수 내 포함된 222 Rn 농도를 측정하는데 보다 정확한 측정을 위한 방법을 알아보고자 한다. 실험은 알파, 베타 펄스의 분석이 용이한 펄스파형분석 기능을 가진 저 준위 액체섬광계수기를 이용하여 실험하였다. 지하수 시료와 혼합하는 섬광체의 조제, 유효기간은 시간이 지날수록 검출값은 낮아지고, 에너지 스펙트럼도 낮은 쪽으로 channel 이동이 있었다. 섬광체의 구입시기가 오래 될수록, 개봉한 후 방치시간이 지날수록 검출값이 낮아짐을 확인했다. 사용목적이 다른 섬광체를 사용했을 경우 channel 이동으로 에너지를 확인할 수 있다. The various environmental issues arose with the development of today's economy. naturally, people were increased interest in environment and the importance of research on drinking water and contamination are emerging especially. A number of country areas, uranium and 222 Rn in ground water have been detected to people using as drinking water. So this study evaluated the way for more accurate measurements than when measuring 222 Rn concentrations in the ground water containing. the experiment was performed using the low-level liquid scintillation counter with an alpha, beta analysis easy PSA function of pulse. the scintillator as the preparation of the ground water samples are mixed, the measure value detection is lowered over prepare period and expiration date. Energy spectrum was also moved to a lower side channel. As a long time to buy the scintillator and over time after opening, it was confirmed that detection is lowered. if the purpose is to use a different scintillator can see the energy through the channel change.